Hedging foreign exchange rate risk: Multi-currency diversification - Susana Álvarez-Díez; Eva Alfaro-Cid; Matilde Fernández-Blanco (European Journal of Management and Business Economics (EJM&BE), 2016)
This article proposes a multi-currency cross-hedging strategy that minimizes the exchange risk. The use of derivatives in small and medium-sized enterprises (SMEs) is not common but, despite its complexity, can be interesting for those with international activities. In particular, the reduction in the exchange risk borne through the use of natural multi-currency cross-hedging is measured, considering Conditional Value-at-Risk (CVaR) and Value-at-Risk (VaR) for measuring market risk instead of the variance. CVaR is minimized using linear programmes, while a multiobjective genetic algorithm is designed for minimizing VaR, considering two scenarios for each currency. The results obtained show that the optimal hedge strategy that minimizes VaR is different from the minimum CVaR hedge strategy. A very interesting point is that, just by investing in other currencies, a significant risk reduction in VaR and CVaR can be obtained.
Keywords: G11; G32; C63; 650; Conditional Value-at-Risk; Cross-hedging; Multi-currency diversification; Multiobjective genetic algorithm; Value-at-Risk